Pilot testing a digital pet avatar for older adults - Chi, Nai-Ching (Geriatr Nurs, 2017)
Social isolation in older adults is a major public health concern. An embodied conversational agent (ECA) has the potential to enhance older adults’ social interaction. However, little is known about older adults’ experience with an ECA. In this paper, we conducted a pilot study to examine the perceived acceptance and utility of a tablet-based conversational agent in the form of an avatar (termed “digital pet”) for older adults. We performed secondary analysis of data collected from a study that employed the use of a digital pet in ten older adults’ homes for three months. Most of the participants enjoyed the companionship, entertainment, reminders, and instant assistance from the digital pet. However, participants identified limited conversational ability and technical issues as system challenges. Privacy, dependence, and cost were major concerns. Future applications should maximize the agent’s conversational ability and the system’s overall usability. Our results can inform future designs of conversational agents for older adults, which need to include older adults as system co-designers to maximize usability and acceptance.